A 100 Ma bimodal composite dyke complex in the Jiamusi Block, NE China: An indication for lithospheric extension driven by Paleo-Pacific roll-back - Sun, M.; Chen, H.; Zhang, F.; Wilde, Simon; Dong, C.; Yang, S. (Elsevier BV, 2013)
A 125 m-wide bimodal composite dyke complex, consisting of rhyolite and dolerite dykes, was emplaced into Cretaceous volcanic strata of the Songmuhe Formation in the Jiamusi Block of NE China. The dolerite dykes are sub-vertical, strike north-south, and intruded into both the country rocks and rhyolite dykes soon after the latter solidified. SHRIMP zircon U–Pb dating shows that the rhyolite dykes were emplaced at 100 ± 2 Ma and the dolerite dykes were also most likely emplaced at 100 ± 2 Ma. The rhyolite is characterized by enrichment in large-ion lithophile elements (LILE) and light rare earth elements (LREE), and depletion in high-field strength elements (HFSE). It shows a significant negative Eu anomaly, and has εNd(t) values ranging from 0.49 to 1.66 and two groups of initial 87Sr/86Sr ratios at 0.7045 and 0.7061. The rhyolite displays the compositional signature of Peraluminous Ferroan Granitoid, indicating it was derived by either differentiation of basalt and/or low pressure partial melting of crust. The dolerite is also characterized by enrichment in LILE and LREE, and depletion in HFSE. It has a weak negative Eu anomaly and has εNd(t) = − 1.22 to + 3.26, and (87Sr/86Sr)i = 0.7057–0.7074.The dolerite originated from partial melting of lithospheric mantle which was affected by subducted oceanic crust, and experienced different amounts of crustal contamination. Such bimodal dyke complexes are an important indicator of crustal extension under the influence of mantle processes. Thus the dyke complex in the Jiamusi Block indicates mid-Cretaceous intra-plate extension in NE China related to the subduction of the paleo-Pacific plate along the eastern Eurasian continental margin. When compared with Mesozoic bimodal magmatism further to the west, our new data support a temporal eastward migration of magmatism over a distance >1000 km from ~160 Ma to ~100 Ma. This was most likely associated with roll-back of the paleo-Pacific Plate and consequent upwelling of asthenospheric mantle